Preparation of nano-microfibers with a different polymers - AL-Tememee, N. A.A. (Iraqi Journal of Physics, 2011)
In this research, nanofibers have been prepared by using an electrospinning method. Three types of polymer (PVA, VC, PMMA) have been used with different concentration. The applied voltage and the gap length were changed. It was observed that VC is the best polymer than the other types of polymers.